The Fibonacci numbers are 0, 1, 1, 2, 3, 5, 8, 13...; starting with 0 and 1, each number is the sum of the two previous numbers.
The Lucas numbers follow the same rule, but start with 2 and 1: 2, 1, 3, 4, 7, 11, 18,...
What's the sum of the first k Lucas numbers?
What's the sum of the squares of the first k Lucas numbers?
(In reply to
Generalized! by nikki)
Ack! I was too hasty and didnt check the sum of the first k Nikki numbers thoroughly. I assumed it was uninteresting. Here are the real answers, along with their proofs.
For any series defined as follows:
N(1) = a
N(2) = b
For k>2, N(k) = N(k-1) + N(k-2)
The following is true:
The sum of the first k Nikki numbers is
N(k+2) N(2) = N(k+2) b
The sum of the squares of the first k Nikki numbers is
N(k)*N(k+1) + N(1)*[N(1) N(2)]
Or
N(k)*N(k+1) + a*(ab)
First Proof: SN(k) = N(k+2) N(2) Base case.
SN(1) = N(1)
Using our proposed formula,
SN(1) = N(1+2) N(2) = N(3) N(2).
SN(1) = [N(2) + N(1)] N(2)
SN(1) = N(1).
So the formula is true for the base case.
Inductive step.
Lets suppose that SN(k) = N(k+2) N(2) is true.
We expect to prove that SN(k+1) = N(k+3) N(2)
SN(k+1) = N(0) + N(1) + N(2) +
N(k+1) + N(k) + N(k+1)
SN(k+1) = SN(k) + N(k+1)
SN(k+1) = N(k+2) N(2) + N(k+1)
Since N(k) = N(k-1) + N(k-2) is the same thing as saying N(k+3) = N(k+2) + N(k+1)
SN(k+1) = N(k+3) N(2)
QED
Second Proof: SSN(k) = N(k)*N(k+1) + N(1)*[N(1) N(2)]
Base case.
SSN(1) = N(1)^2
Using our proposed formula,
SSN(1) = N(1)*N(1+1) + N(1)*[N(1) N(2)]
SSN(1) = N(1)*N(2) + N(1)^2 N(1)*N(2)
SSN(1) = N(1)^2
So the formula is true for the base case.
Inductive step.
Nets suppose that SSN(k) = N(k)*N(k+1) + 2
We expect to prove that SSN(k+1) = N(k+1)*N(k+2) +2
SSN(k+1) = N(0)^2 + N(1)^2 + N(2)^2 +
N(k+1)^2 + N(k)^2 + N(k+1)^2
SSN(k+1) = SSN(k) + N(k+1)^2
SSN(k+1) = N(k)*N(k+1) + N(1)*[N(1) N(2)] + N(k+1)^2
SSN(k+1) = N(k+1)*[N(k) + N(k+1)] + N(1)*[N(1) N(2)]
SSN(k+1) = N(k+1)*[N(k+2)] + N(1)*[N(1) N(2)]
SSN(k+1) = N(k+1)*N(k+2) + N(1)*[N(1) N(2)]
QED
|
Posted by nikki
on 2004-10-08 09:15:31 |